Characterization of Aminoacyl-tRNA Synthetases in Chromerids - Sharaf, Abdoallah; Gruber, Ansgar; Jiroutová, Kateřina; Oborník, Miroslav (Genes, 2019)
Aminoacyl-tRNA synthetases (AaRSs) are enzymes that catalyze the ligation of tRNAs to amino acids. There are AaRSs specific for each amino acid in the cell. Each cellular compartment in which translation takes place (the cytosol, mitochondria, and plastids in most cases), needs the full set of AaRSs; however, individual AaRSs can function in multiple compartments due to dual (or even multiple) targeting of nuclear-encoded proteins to various destinations in the cell. We searched the genomes of the chromerids, Chromera velia and Vitrella brassicaformis, for AaRS genes: 48 genes encoding AaRSs were identified in C. velia, while only 39 AaRS genes were found in V. brassicaformis. In the latter alga, ArgRS and GluRS were each encoded by a single gene occurring in a single copy; only PheRS was found in three genes, while the remaining AaRSs were encoded by two genes. In contrast, there were nine cases for which C. velia contained three genes of a given AaRS (45% of the AaRSs), all of them representing duplicated genes, except AsnRS and PheRS, which are more likely pseudoparalogs (acquired via horizontal or endosymbiotic gene transfer). Targeting predictions indicated that AaRSs are not (or not exclusively), in most cases, used in the cellular compartment from which their gene originates. The molecular phylogenies of the AaRSs are variable between the specific types, and similar between the two investigated chromerids. While genes with eukaryotic origin are more frequently retained, there is no clear pattern of orthologous pairs between C. velia and V. brassicaformis.
Keywords: protein localization; Phylogeny; Alveolata; Aminoacyl tRNA synthetase (AaRS); Vitrella brassicaformis; mitochondrion; Protozoan Proteins; chloroplast; nucleus; protozoální proteiny; Amino Acyl-tRNA Synthetases; Chromera velia; aminoacyl-tRNA-synthetasy; evolution; fylogeneze